203k views
1 vote
X+3

=
ov*-
- (3)
ox-()*+1
O
+1
O
or-()***
X-1
+3
oy- ()
+1
-3

X+3 = ov*- - (3) ox-()*+1 O +1 O or-()*** X-1 +3 oy- () +1 -3-example-1

2 Answers

5 votes


\\ \sf\longmapsto y=\left((1)/(2)\right)^(x-3)+1

Graph attached

X+3 = ov*- - (3) ox-()*+1 O +1 O or-()*** X-1 +3 oy- () +1 -3-example-1
User Polku
by
5.5k points
2 votes


▪▪▪▪▪▪▪▪▪▪▪▪▪  {\huge\mathfrak{Answer}}▪▪▪▪▪▪▪▪▪▪▪▪▪▪

The Correct choice is ~


\boxed{y = \bigg({(1)/(2) \bigg) }^(x - 3) + 1}

User Punit S
by
5.5k points